Semantics of the Russian Verbs of Destruction in Contemporary Linguistics: Семантический Анализ Глаголов Деструкции Русского Языка В Современной Лингвистике (Journal of the College of Languages (JCL), 2021)
The article states that the Russian verbs of destruction belong to the lexical-semantic group of physical impact. They include verbs with the meaning of “damage” and “destroy”. It is emphasized that each of these groups is relatively independent; the cut line between them is fuzzy and arbitrary. It is postulated that when the object is completely destroyed, then the verb has the meaning of “destruction”, and when the object is partially destroyed, then the verb has the meaning of “damage”. It is this feature that individualizes the meaning of verbs. The study distinguishes between the groups and the nature of the object as- animate / inanimate. The object of the action of the “destruction” can only be inanimate, and the object of the action of “damage” and “destruction” can be both animate and inanimate objects.АннотацияВ статье утверждается, что глаголы деструкции относятся к лексико-семантической группе физического воздействия. Они включают глаголы со значением «повредить» и «уничтожить». Акцентируется внимание, что каждая из этих групп относительно самостоятельная, граница между ними нечеткая и условная. Постулируется, что если объект совсем разрушен, то глагол имеет значение «уничтожить», если частично – то глагол имеет значение «повредить». Именно этот признак индивидуализирует значения глаголов. В нашем исследовании утверждается, что отличает эти группы и характер объекта – одушевленное / неодушевленное. Объектом воздействия действия «разрушать» может быть только неодушевленные, а объектом действия «повредить» и «уничтожить» может быть как существо, так и неодушевленные предметы.